Como a avaliação diagnóstica realizada pela seduc influencia na prática pedagógica do professor de matemática - Loiola, Fabiano Oliveira de (2021)
Diagnostic assessment is an important pedagogical resource necessary for the teacher to become aware of the student's understanding according to a set of skills and competences on a certain curriculum element, aiming to plan their intervention action, as per Luckesi (2011) precept. This situation, along with the use of external assessments as pedagogical support, has motivated the development of researches with the intention of improve learning. For example, Silva (2019) and Ferreira Filho (2020) seek to understand the reality in which they are inserted, proposing solutions within each context. The research studied the Diagnostic Assessment fulfilled in secondary school state network of Ceará. Therefore, a semi-open questionnaire was applied in three schools in the city of Quixadá with different teaching modalities (a Professional School, a Full-Time and a Regular School), in which the results were achieved, trying to observe how this evaluation was carried out in the teaching and practice of the mathematics teacher. The results achieved indicate the beginning of a conversation between the actors involved in the evaluation process, promoting students learning